Suran's Re-Existence for Intergenerational Eco-Efforts in Kahuripan Hamlet - Wisnu Sapto Nugroho; Izhak Y.M Lattu; Tony Tampake; Spyridon Tsitsigkos (Jurnal Mamangan, 2024)
This article aims to explore the existence of Suran in the appreciation of the people of Kahuripan hamlet, Kalirejo village, Bagelen District, Purworejo Regency, Central Java for the realization of intergenerational ecology (intergenerational eco). The research approach used is a qualitative approach with narrative-descriptive data analysis techniques. Data were collected through interviews and literature studies. Research sources came from intergenerational Kahuripan villagers who knew and experienced the Suran tradition. The theory used as an analytical knife is Anthony Giddens' structuration theory and generation theory. This study found that three layers of generations do not know the background of abstinence and Suran rituals, but they believe that Suran is an ancestral heritage that must be preserved. People consider the month of Sura as a sacred month. The sacredness of Sura makes people do "reresik" (cleaning themselves, cleaning life), fasting and abstaining from holding celebrations, abstaining from traveling far without a clear purpose, and pasa mutih. All of this is done as a practice that keeps away from seeking pleasures so that fuel, electricity, water and other natural resources are saved. Data analysis proves the importance of Suran's re-existence to realize ecology carried out by all people at the same time and continuously. The acts of abstinence in the Suran rite show the strength of the ecological movement carried out by all generations (intergenerational). In the end, this research concludes that the re-existence of Suran as a collective life of the Kahuripan hamlet community can act as an intergenerational eco-movement.